A rare case of lichenoid sarcoidosis mimicking papular amyloidosis - Preema Sinha; Saikat Bhattacharjee; Deep Kumar Raman; Aradhana Sood (Wolters Kluwer Medknow Publications, 2020)
Cutaneous lesions in sarcoidosis are seen in nearly 20-30% and include lesions like papules, nodules, plaques, infiltrated scars, and erythema nodosum. Lichenoid variants of cutaneous sarcoidosis, a type of papular variant is quite rare. Herein we report a case of lichenoid sarcoidosis in a 40-year-old male who presented with raised itchy lesions over his legs and lower back of 8 years duration.